Investigation Of The Process Of Copolymerization Of Methacrylic Acid With N-Morpholine-3-Chlorous Isopropylacrylate (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
The article shows studies of the reaction of radical copolymerization in the presence of the initiator azobisisobutyronitrile in dimethylformamide medium, linear copolymers of methacrylic acid with N-morpholine-3-chloroisopropylacrylate were synthesized in the temperature range of 60-70 °C. The influence of the concentration of the initiator on the copolymerization process was studied, and the influence of the ratio of the initial monomers was also established. The composition and structure of the synthesized copolymers were studied by FT-IR spectroscopy. Thermogravimetric studies were carried out and it was found that the curve of the binary copolymer has a wide endothermic peak in the region of 206°C, this is due to the formation of intermolecular anhydride bonds, which contribute to an increase in its thermal stability